1978
DOI: 10.1207/s15328023top0502_1
|View full text |Cite
|
Sign up to set email alerts
|

Mastery: The Essential Essential in PSI

Abstract: Four studies were conducted in order to clarify the importance of student proctors and mastery performance in PSI systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…It is equally likely that the student IS also shaping the proctor's behavior" (p. 62). Contrary to previous studies, Caldwell et al (1978) found no evidence that having student proctors improved student performance. A major difference between their study and other studies was that their proctors did not have the power to accept approximations to the answer nor could the students defend their answers (quizzes were all multiple-choice).…”
Section: Student Proctors and Cheatingcontrasting
confidence: 99%
See 3 more Smart Citations
“…It is equally likely that the student IS also shaping the proctor's behavior" (p. 62). Contrary to previous studies, Caldwell et al (1978) found no evidence that having student proctors improved student performance. A major difference between their study and other studies was that their proctors did not have the power to accept approximations to the answer nor could the students defend their answers (quizzes were all multiple-choice).…”
Section: Student Proctors and Cheatingcontrasting
confidence: 99%
“…A major difference between their study and other studies was that their proctors did not have the power to accept approximations to the answer nor could the students defend their answers (quizzes were all multiple-choice). Caldwell et al (1978) argued further that "an alternative interpretation a5 to why proctoring in these other studies reduced the number of tests taken is that the student shaped the proctors to accept approximations to the correct response rather than only correct responses" (p. 62). Further evidence comes from a study concerned with the effects of self-grading.…”
Section: Student Proctors and Cheatingmentioning
confidence: 99%
See 2 more Smart Citations
“…written objectives, and mastery criteria are most important, and that proctors are considerably less important (Caldwell et al, 1978;J. A. Kulik et al, 1976;Williams, 1976).…”
Section: Proctorsmentioning
confidence: 99%